A generalized endogenous grid method for non-concave problems - Giulio Fella (Queen Mary University of London, School of Economics and Finance, 2011)
This paper extends Carroll's (2006) endogenous grid method and its combination with value function iteration by Barillas and Fernández-Villaverde (2007) to non-concave problems. The method is illustrated using a consumer problem in which consumers choose both durable and non-durable consumption. The durable choice is discrete and subject to non-convex adjustment costs. The algorithm yields substantial gains in accuracy and computational time relative to value function iteration, the standard solution choice for non-concave problems.
Keywords: C63; 330; endogenous grid method; non-concavity; Konsumentenverhalten; Dauerhaftes Konsumgut; Theorie